EKSISTENSI DAN PERAN AGEN BRILINK DI KECAMATAN LOLI KABUPATEN SUMBA BARAT - Lede, Asriel; Ballo, Fransina Weli (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 8 (2024): Vol.13.No.8. AGUSTUS 2024 [545-633], 2024)
This research aims to analyze the existence and role of Brilink agents in facilitating banking transactions in the community in Loli sub-district. This research uses qualitative research with an empirical study research approach. Data collection was carried out through interviews with informants about the role of BRILink agents in facilitating banking transactions in the community. Data collection was also carried out by means of observation and documentation. The results of this research show that the existence of BRILink agents in Loli sub-district plays a very important role for the community in banking transaction activities such as sending and withdrawing money, topping up electricity credit, cellphone credit or topping up balances. This is because before there were BRILink agents, people had to travel all the way to the capital city. West Sumba to carry out banking transactions which require a lot of money and also take a long time, therefore BRILink agents are the best solution and play an important role for the people in Loli sub-district.